Acidogenic and methanogenic properties of corn straw silage: Regulation and microbial analysis of two-phase anaerobic digestion. (July 2020) - Li, Yan; Hua, Dongliang; Xu, Haipeng; Jin, Fuqiang; Mu, Hui; Zhao, Yuxiao; Fang, Xu
Graphical abstract: Highlights: LBR and UASB were integrated to convert CSS in two-phase anaerobic digestion. pH controlling strategy was adopted to regulated the acidogenic efficiency. The dominant VFAs were HAC and HPr and the maximum VFAs yield was obtained at pH 8. OLR of ≤8 g COD/L·d was well operated and methane yield was 143.4 mL/g VS. The predominant bacterial and archaeal communities were analyzed. Abstract: Corn straw silage (CSS) is one of the organic solid residues available for biogas production. The aim of this study was to investigate the possibility and optimal controlling strategy for anaerobic digestion (AD) of CSS. Four leaching bed reactors (LBR) were operated at different pH. Maximum volatile fatty acids (VFAs) concentration of 19.34 g/L was reached at pH 8.0 with acetic and propionic acids as dominant VFAs. The subsequent microbial analysis indicated that abundant bacteria were Firmicutes, Bacteroidetes and Proteobacteria . UASB as methanogenic reactor was integrated with the LBR. The organic loading rate (OLR) could reach 8 g COD/L·d with effective conversion of VFAs. Acetotrophic Methanosaeta and hydrogenotrophic Methanobacterium played major roles in methanogenic process. In the whole process, the results showed that methane yield of 143.4 mL CH4 /g volatile solid (VS) was obtained. pH and OLR controls in two-phase AD were feasible for methane production from CSS.